Cardiovascular System Under Simulated Weightlessness: Head-Down Bed Rest vs. Dry Immersion - Amirova, Liubov; Navasiolava, Nastassia; Rukavishvikov, Ilya; Gauquelin-Koch, Guillemette; Gharib, Claude; Kozlovskaya, Inessa; Custaud, Marc-Antoine; Tomilovskaya, Elena (Frontiers in Physiology, 2020)
Background. The most applicable human models of weightlessness are Head-Down Bed Rest (HDBR) and Dry Immersion (DI). However, a detailed comparison of the models was not carried out. Objectives. We compared changes in central hemodynamics, autonomic regulation, plasma volume and water balance induced by HDBR and DI. Methods. 11 subjects participated in 21-day HDBR, and 12 – in 3-day DI. During exposure, water balance (the difference between water intake and diuresis), blood pressure and heart rate were registered daily. Plasma volume evolution was estimated by Dill-Costill method. Before and after exposure Lower Body Negative Pressure -Tilt Test was conducted for assessment of orthostatic tolerance time, central hemodynamics responses to orthostatic stimuli and autonomous regulation. Results. In most of studied parameters, the changes were codirectional, differing, however, in their extent. Systolic blood pressure (dropped 17 mmHg) and total peripheral resistance (dropped 0,11 au) after HDBR were changed more than after DI (decrease of 10 mm Hg and did not change, respectively). The orthostatic tolerance time decreased in both groups - to 14,2 ± 3,1 min (vs. 27.9 ± 2.5 min at baseline) in the group of 21-day HDBR and to 8.7 ± 2.1 min (vs. 27.7 ± 1.2 min at baseline) – in the group of 3-day DI. Conclusions. In general, cardiovascular changes during 21-day HDBR and 3-day DI were co-directed. Frequently, changes after 3-day DI were equal to or exceeded changes after 21-day HDBR. Significantly stronger effects of DI on cardiovascular function can be caused by hypovolemia and support unloading (supportlessness).